4.9k views
3 votes
F(x) = 3x - 7 and g(x) = -2x - 6. Find (f + g)(x). Show steps.

2 Answers

6 votes
For this, plug in x for both of the equations(so you don’t do anything because that is how it is written) and then you add them. X-13
User No Hay Problema
by
5.1k points
5 votes

Answer:

x - 1

Explanation:

(f + g)(x)=f(x) + g(x)

(f + g)(x)=(3x - 7) + (-2x - 6)

(f + g)(x)= 3x - 7 - 2x + 6

(f + g)(x)= 3x - 2x - 7 + 6

(f + g)(x)= x -1

User Endoro
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.